Local and regional factors affecting atmospheric mercury speciation at a remote location. Issue 5 (9th August 2007) - Manolopoulos, Helen; Schauer, James J.; Purcell, Mark D.; Rudolph, Todd M.; Olson, Mark L.; Rodger, Bruce; Krabbenhoft, Dave P.
Abstract : Atmospheric concentrations of elemental (Hg 0 ), reactive gaseous (RGM), and particulate (PHg) mercury were measured at two remote sites in the midwestern United States. Concurrent measurements of Hg 0, PHg, and RGM obtained at Devil's Lake and Mt. Horeb, located approximately 65 km apart, showed that Hg 0 and PHg concentrations were affected by regional, as well as local sources, while RGM was mainly impacted by local sources. Plumes reaching the Devil's Lake site from a nearby coal-fired power plant significantly impacted SO2 and RGM concentrations at Devil's Lake, but had little impact on Hg 0 . Our findings suggest that traditional modeling approaches to assess sources of mercury deposited that utilize source emissions and large-scale grids may not be sufficient to predict mercury deposition at sensitive locations due to the importance of small-scale sources and processes. We suggest the use of a receptor-based monitoring to better understand mercury source–receptor relationships.